Extending Schumacher's concept of total accounting and accountability into the 21st century - Saravanamuthu, Kala; Lehman, Cheryl R. (Emerald, 2009)
A decade on from Schumacher's 1997 work, there are renewed calls for a paradigm shift from the metaphysics of materialism that informs conventional thinking, to holistic theorisations of how we should engage with the other. Twenty-first century frameworks of accountability should emancipate society from the hegemony of neoclassical economics. This special issue posits Schumacher's Middle Way thinking in the context of growing concerns about global warming and climatic changes and, teases out its implications for holistic accountability by introducing readers to the science of climate change and its implications for managing natural resources, and integrating 'western' and 'eastern' tenets of holistic knowledge without dichotomising them into 'either or' frameworks.
Keywords: Accounting.; Finance.; elektronické knihy; electronic books